Notes on some tanypods from Lake Winnipeg, Manitoba, Canada (Diptera: Chironomidae) - Sæther, Ole A. (Zootaxa, 2011)
The Tanypodinae from Lake Winnipeg, Manitoba, Canada are listed and taxonomic and ecological notes given. The males of Paramerina fragilis (Walley) and Helopelopia pilicaudata (Walley), and the immatures of Telopelopia okoboji (Walley) are redescribed. The larvae of cf. Conchapelopia currani (Walley) and cf. Helopelopia pilicaudata are described.